DESIGN OF INFORMATION SYSTEM OF CAREER CENTER ALUMNI STMIK MUSIRAWAS LUBUKLINGGAU MOBILE WEB BASE - Tri Hasanah Bimastari Aviani; Davit Irawan; Asep Toyib Hidayat (IJISCS (International Journal of Information System and Computer Science), 2019)
The problem in this study is that the mobile web-based career center information system with the breadth first search method does not yet exist on the STMIK Musi Rawas Lubuklinggau campus. Just simply sticking a piece of information on job vacancies on campus campus. This research uses the waterfall system development method and data collection by conducting data collection techniques which are observing (Observation), Question and Answer (Interview), Documentation and Literature Study. The results of this study produce a mobile web-based career center information system using the PHP programming language, and a database using MySQL. It can be concluded that the information system can help STMIK Alumni Musirawas Lubuklinggau find information on job vacancies through the career center information system, and the university can also provide information on available job openings.